SURVEI PERILAKU PENCEGAHAN COVID-19 PADA IBU MAHASISWA NERS STIKes SANTA ELISABETH MEDAN - Lindawati Simorangkir; Ice Septriani Saragih; Mardiati Barus; David Sumanto Napitupulu (Jurnal Ilmiah Keperawatan IMELDA, 2021)
COVID-19 is categorized as an infectious disease. The increase in the number of COVID-19 cases took place quite quickly and spread outside the Wuhan area and other countries. break the chain of transmission of COVID-19 by calling for the Independent Health Care Family Movement (GERGAJI). The research design used is descriptive with the Cross Sectional method. The population in this study were all students of the Nursing Study Program level II STIKes Santa Elisabeth Medan. Sampling in the study using the Total Sampling technique with a total sample of 84 respondents. The researcher collected data using a google form in the form of a questionnaire consisting of 16 statements regarding the application of the Covid-19 prevention saw method. The results showed that most of the respondents' behavior always used a mask when leaving the house, as much as 72.6%. Most of the respondents' behavior is always washing hands with soap, as much as 47.6%. Most of the respondents' behavior always kept their distance, as much as 52.4%. Most of the respondents' behavior always uses hand sanitizer, as much as 51.2%. Most of the respondents' behavior is always cleaning the house, as much as 82.1%. Most of the respondents' behavior is always doing activities at home, as much as 32.1%. Health workers need to increase public awareness through communication and education in preventing Covid-19 so that people are able to prevent Covid-19.